Leadership Style and Employee Motivation: A Study of Saudi Arabian Work Environment - Altheeb, Saad Al (2020)
Leaders motivate employees through setting in place structures aimed at taking full advantage of employee’s potential, organization resources and providing direction. Conversely, they can severely cause difficulty in inspiring confidence, buying into firm’s goals, promoting alignment and fostering collaborative environment. Therefore, this research aims at investigating relationship leadership style and motivation of employees. An intensive review of literature has been conducted highlighting employee motivation, leadership style (Authoritarian, Paternalistic, Transformational, Laissez-faire). The data were collected through questionnaire which was distributed to government employees working in Alkharj (Riyadh region) and 130 valid responses were received. SPSS 22 was used to carry out statistical analysis and the results indicated an overall positive significance of leadership styles and motivation. The overall impact of leadership styles together on motivation was found as 66.5% (R2=0.665). The unique effects of each Paternalistic, Transformational and Laissez-faire style on motivation was found positive and significant. Whereas, the relationship between authoritarian leadership style and motivation was found insignificant. It is recommended that leaders in Saudi Arabia work environment must follow paternalistic and transformational leadership styles to enhance motivation level of their employees.